Essence of leadership of Filipino women presidents in higher education - Patriarca, Marian Christine Valdepenas; Muega, Maricris Acido; Javiniar, Joel C.; Acosta, Sherlyne A.; Cajilig, Norma G.; Manzano, Virgilio U. (Quezon City College of Education, University of the Philippines Diliman, 2015)
This qualitative study utilized phenomenology as a method of research using a constructivist lens. It involved ten (10) women presidents of higher education institutions (HEIs) based in Metro Manila who held the position for a minimum of three (3) years to thirteen (13) years. The women presidents came from two (2) state universities and eight (8) private HEIs. Data were gathered using one-on-one personal semi-structured in-depth interviews utilizing open-ended questions which lasted approximately between forty (40) minutes to 1 hour and fifteen minutes (1.15 hours).
The Modified Van Kaam method of phenomenological analysis by Moustakas (1994) was used for analyzing the data. It involved seven (7) steps – 1) horizonalization of data through listing and preliminary grouping; 2) identification of the invariant constituents by reduction and elimination; 3) clustering and thematizing the invariant constituents as a result of thematic labeling; 4) final identification of invariant constituents; 5) construction of textural description; 6) construction of structural description; and, 7) construction of textural-structural description. Finally, a composite textural-structural description of the meanings and essences of the lived experience of the women leaders in HEIs was constructed.
There were forty-five (45) invariant constituents that emerged from the
data and clustered into six (6) themes. These are 1) women academic presidents as leaders; 2) women academic presidents as fostering relationships; 3) women academic presidents as trailblazers; 4) women academic presidents’ challenges; 5) women academic presidents’ value system; and, 6) women academic presidents’ work-life balance.
From the invariant constituents and themes, there were (five) 5 essences that emerged from the findings of the data which is summed up in the word PRIDE which stands for Passion, Relationships, Integrity, Discipline and Excellence. Hence, the essence of their lived experience is “PRIDE of Women Leaders in HEIs”. The word PRIDE was very fitting because these women leaders found a deep pleasure and fulfillment brought about by their accomplishments in their respective institutions. They did not deem their gender as an issue for not being able to fully assume successfully their leadership position. Instead, they executed their roles with honor and dignity and were conscious of the fact that gender has nothing to do with a person’s success or failure. Leadership is not about being male or female, it all boils down to the individuality and uniqueness of a person.
Thesis
Includes bibliographical references (pages 293-303)
Keywords: Women presidents -- Philippines -- Manila Metropolitan Area; Women as leaders -- Philippines -- Manila Metropolitan Area; Educational leadership -- Philippines -- Manila Metropolitan Area; State universities and colleges -- Philippines -- Manila Metropolitan Area -- Administration; Universities and colleges -- Philippines -- Manila Metropolitan Area -- Administration